GASIFICATION OF COAL-PETCOKE-BIOMASS BLENDS - MOHAMAD NAJIB, NUR KHADIJAH (2014)
Gasification is one efficient alternative of producing fuel syngas by converting coal or wastes into useful biofuels. This process has been widely used in the last three centuries especially in energy and chemical applications. In this research we have focussed in optimizing the gasification parameters when using coal, petroleum coke and biomass as fuel to produce syngas. The gasification tests for coal and fuel blends were conducted using Atmospheric Bubbling Fluidized Bed Gasifier (ABFG) in controlled Equivalence Ratio (ER) and air as fluidizing agent. From the earlier fuel characterization studies done, it is seen that biomass has the highest volatile matter but differ principally for their fixed carbon content which coal has the highest fixed carbon and ash content compared to these three fuels. The gasification process was then modelled using thermodynamic equilibrium model method and simulated with Aspen HYSYS 2004.1 simulation software.